Anatomic Delineation of Tarsal Tunnel Innervation via Ultrasonography. (4th December 2017) - Iborra, Alvaro; Villanueva, Manuel; Barrett, Stephen L.; Rodriguez‐Collazo, Edgardo; Sanz, Pablo
Abstract : Objectives: High‐resolution ultrasonography (US) can play an important role in studying nerves, as it has several advantages. Entrapments of distal tibial nerve branches can be mapped out or diagnosed with selective anesthetic blocks, and US can guide therapeutic procedures, such as radiofrequency ablation and selective infiltrations of specific nerve branches. The aim of this study was to verify that US is an effective method for accurately locating the posterior tibial nerve and its terminal branches, such as the medial calcaneal branch, the first calcaneal branch, and the medial and lateral plantar nerves. Methods: In this study, we analyzed the correlation between US mapping and real anatomy after cadaveric dissection, assessing the distribution and variability of the tibial nerve and its terminal branches. We used 12 fresh anatomic specimens of the foot and ankle, including the calf. A high‐resolution US study of the tibial nerve and its branches was performed. Results: The results of the US studies of the anatomic specimens were drawn as paper diagrams and in data collection tables. Both were completed twice per anatomic specimen, first using the results of the US study and second using the results from dissection of the anatomic specimens; this approach enabled us to compare the results and verify whether the US study and the dissection correlated on the topography of the tibial nerve and its terminal branches. We found almost total agreement between the US and dissection results, with no significant differences between the evaluations. Conclusions: On the basis of this work, we can conclude that high‐resolution US is almost 100% effective as a tool for identifying the tibial nerve and its branches, enabling the specialist to make diagnoses or perform selective treatments on each nerve branch and even to design surgical interventions by observing the patient's anatomy before performing the dissection